Modeling the tensile steel reinforcement strain in RC-beams subjected to cycles of loading and unloading. (1st November 2016) - Xu, Tengfei; Castel, Arnaud; Gilbert, R. Ian; Murray, Angus
Highlights: Tests involving cycles of loading and unloading on eleven RC beams are reported. A model of the effective strain in the tensile reinforcement is presented. New effective and average moment of inertia models are suggested. The new model is validated by experimental data from this study and elsewhere. Abstract: Tension stiffening affects the strain distribution along the tensile reinforcement in a cracked reinforced concrete beam and in the tensile concrete between cracks. It also affects the overall stiffness and hence the deflection of the beam. In this paper, the results of experiments on eleven reinforced concrete beams with reinforcement ratios between 0.56% and 0.88% are reported. The overall strain in the reinforcement and the load-deflection response under both monotonic loading and cycles of loading and unloading were measured for each beam. Based on the experimental results, a model of the effective strain in the reinforcement is presented and is used to assess the effective moment of inertia of reinforced concrete beams subjected to in-service monotonic loading. Measurements from the test beams were used to calibrate a model of the steel-concrete interface damage caused by cycles of loading and unloading. The comparisons between predicted and measured overall stiffness and load-deflection responses show the validity of the present model.